1999
DOI: 10.1086/315061
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity of Tumor Necrosis Factor/Lymphotoxin‐α–Deficient Mice toCryptococcus neoformansInfection despite Increased Levels of Nitrite/Nitrate, Interferon‐γ, and Interleukin‐12

Abstract: The cytokine network and infection severity were characterized during disseminated cryptococcosis in tumor necrosis factor (TNF)- and lymphotoxin (Lt)-alpha-deficient mice. On day 16, the fungus burden was higher and median survival time was reduced, as was polymorphonuclear leukocyte infiltrate in the brains of knockout mice. TNF/Lt-alpha-deficient mice had lower levels of interleukin (IL)-6 in lungs and brains, IL-1beta, and the chemokine KC in brain and spleen and of the chemokine monocyte chemoattractant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…TNF-␣ and IL-12 production by macrophages is also required for IFN-␥ production during Listeria monocytogenes infection (36), while neutralization of TNF-␣ with a soluble TNF receptor fusion protein can inhibit Th1 polarization in vitro through the inhibition of IL-12 and IFN-␥ (2). In contrast, a report by Rayhane et al has shown that TNF-␣ is not required for induction of IFN-␥ and IL-12 during C. neoformans infection (30). However, these differences are almost certainly due to different routes of infection (intravenous versus intratracheal), kinetics of cytokine analysis (day 16 versus day 7), and sites analyzed.…”
Section: Discussionmentioning
confidence: 86%
“…TNF-␣ and IL-12 production by macrophages is also required for IFN-␥ production during Listeria monocytogenes infection (36), while neutralization of TNF-␣ with a soluble TNF receptor fusion protein can inhibit Th1 polarization in vitro through the inhibition of IL-12 and IFN-␥ (2). In contrast, a report by Rayhane et al has shown that TNF-␣ is not required for induction of IFN-␥ and IL-12 during C. neoformans infection (30). However, these differences are almost certainly due to different routes of infection (intravenous versus intratracheal), kinetics of cytokine analysis (day 16 versus day 7), and sites analyzed.…”
Section: Discussionmentioning
confidence: 86%
“…TNF-␣ in Cybb tm1 mice may assist in the maintenance of a protective Th1 response. TNF knockout mice are more susceptible to C. neoformans infection (55), and Huffnagle and colleagues (56,57) have demonstrated a significant early role for TNF in leukocyte recruitment of leukocytes and the development of Th1-biased immune response. Indeed, we have previously reported that CpG has been demonstrated to promote a heightened Th1 response to C. neoformans and prevent dissemination to the brain, an effect that was abolished by depleting TNF-␣ (58).…”
Section: Discussionmentioning
confidence: 99%
“…A CNS-specific and TNF-␣-dependent role for IL-6 and IL-1␤ in protection against cryptococcosis is suggested by findings with TNF/lymphotoxin-␣-deficient mice. The markedly reduced survival of TNF/lymphotoxin-␣-deficient mice was associated with a marked reduction in brain levels of IL-6 and IL-1␤, while levels of these cytokines in plasma and other organs were similar in knockout and parental-strain mice, and plasma and tissue levels of IFN-␥ and IL-12 were higher in knockout than in parentalstrain mice (28).…”
Section: Fig 7 Effect Of Depletion Of Cd25mentioning
confidence: 91%